Change in subfoveal choroidal thickness secondary to orthokeratology and its cessation: a predictor for the change in axial length. Issue 3 (4th October 2018) - Li, Zhouyue; Hu, Yin; Cui, Dongmei; Long, Wen; He, Mingguang; Yang, Xiao
Abstract: Purpose: To investigate changes in subfoveal choroidal thickness (SFChT) during orthokeratology (Ortho‐K) lens wear and after its cessation and the association of short‐term change in SFChT with the long‐term eye elongation in Ortho‐K subjects. Design: A prospective clinical trial. Methods: Fifty myopic children aged between 9 and 14 years were enrolled. Twenty‐nine subjects continuously wore Ortho‐K lens for 12 months and discontinued for 1 month. Twenty‐one subjects wearing single vision distance spectacles for 12 months were included as the control group. SFChT was assessed using optical coherence tomography. Ocular parameters, including axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT) and apical corneal power (ACP), were also measured. Results: After 12 months of follow‐up, AL elongation was larger and SFChT change was smaller in the control group compared to the Ortho‐K group (both p < 0.001). In the Ortho‐K group, SFChT increased by 16  μ m from baseline at the 1‐month visit (p < 0.001), and the magnitude of choroidal thickening remained unchanged at the 6‐ and 12‐month visit (p = 0.289). One month after discontinuation of Ortho‐K lens, SFChT and ocular parameters of the anterior segment, including ACP, CCT and ACD recovered to baseline level (All p > 0.05), and AL increased by 0.23 ± 0.18 mm compared to baseline (p = 0.018). SFChT change at 1‐month was negatively associated with AL change at 13‐month (standard β, −0.581, p = 0.001) after adjusting for other influencing factors, including baseline age and the ocular parameters. Conclusion: Subfoveal ChT (SFChT) significantly increased after short‐term Ortho‐K lens treatment and the increase maintained throughout the period of treatment. One month after Ortho‐K lens cessation, SFChT, ACP, CCT and ACD returned to baseline. Short‐term response in SFChT is associated with long‐term change in AL in children undergoing Ortho‐K lens and may be a predictor for the effectiveness of the treatment.